2017
DOI: 10.2174/1567205014666170508121031
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology Based Theranostic Approaches in Alzheimer's Disease Management: Current Status and Future Perspective

Abstract: Background Alzheimer's disease (AD), a cognitive dysfunction/dementia state amongst the elders is characterized by irreversible neurodegeneration due to varied pathophysiology. Up till now, anti-AD drugs having different pharmacology have been developed and used in clinic. Yet, these medications are not curative and only lowering the AD associated symptoms. Improvement in treatment outcome required drug targeting across the blood-brain barrier (BBB) to the central nervous system (CNS) in optimal therapeutic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 146 publications
(193 reference statements)
0
31
0
1
Order By: Relevance
“…In recent years, a variety of nanoparticles have been identified that have been used in drug and gene transfer processes, including platinum, gadolinium-based nanoparticles, gold nanoparticles (AuNPs), iron oxide, cerium oxide nanoparticles, and nanodiamonds. 51,52 Kaushik studied a synergistic effect of nanoparticles (AuNPs, MnNPs, and SPIONs) with wgx-50, effective on the inhibition of amyloid-beta 42 (Aβ-42) (Alzheimer's disease-initiating risk-enhancing protein) and the results showed the inhibitory effect of wgx-50-AuNP on Aβ-42 inhibition. 53 However, in another study by this scientist, he compared nanoparticles to SPIONs as suitable candidates for Aβ inhibition compared to four nanoparticles (AuNPs, MnNPs, cobalt and SPIONs) and stated that SPIONs were more efficient than AuNPs because of their energy bands to inhibit Aβ.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a variety of nanoparticles have been identified that have been used in drug and gene transfer processes, including platinum, gadolinium-based nanoparticles, gold nanoparticles (AuNPs), iron oxide, cerium oxide nanoparticles, and nanodiamonds. 51,52 Kaushik studied a synergistic effect of nanoparticles (AuNPs, MnNPs, and SPIONs) with wgx-50, effective on the inhibition of amyloid-beta 42 (Aβ-42) (Alzheimer's disease-initiating risk-enhancing protein) and the results showed the inhibitory effect of wgx-50-AuNP on Aβ-42 inhibition. 53 However, in another study by this scientist, he compared nanoparticles to SPIONs as suitable candidates for Aβ inhibition compared to four nanoparticles (AuNPs, MnNPs, cobalt and SPIONs) and stated that SPIONs were more efficient than AuNPs because of their energy bands to inhibit Aβ.…”
Section: Discussionmentioning
confidence: 99%
“…With an IL‐1β monoclonal antibody modified SPIONs, it is able to cross the BBB via AMT as a targeted therapy and simultaneous image by MRI . With the combination of high selective antibodies, MNPs have been proved to exhibit a bright prospect to clinical application …”
Section: Imagingmentioning
confidence: 95%
“…Nanorobots can be used to carry thrombin and stop blood flow in tumor vessels, while DNA-based signal amplification methods combined with DNA-integrated gold nanomaterials accurately detect tumor biomarkers [138]. Alzheimer's disease biomarkers can also be detected using nanotechnology both in vitro and in vivo [142]. Detecting small molecules, bacteria, pathogen biomarkers as well as targeted drugs may be enhanced by utilizing the knowledge from the field of DNA nanotechnology in the near future due to the advantages described above.…”
Section: Current Dna-based Approaches Being Developed Towards Diagnosismentioning
confidence: 99%